Stochastic and Nonlinear Dynamic Response of Drillstrings in Deepwater Riserless Casing Drilling Operation - He Li; Guodong Cheng; Shiming Zhou; Wenyang Shi; Jieli Wang (Journal of Marine Science and Engineering)
In order to gain an insight into the stress state of drillstring in riserless drilling conditions with Casing while Drilling (CwD) technology, a stochastic and nonlinear dynamic model of the drillstring under the excitation of the environmental load is established based on Hamilton principle and finite deformation theory. The distribution of tensile stress, bending stress, and effective stress along the axial direction of drillstring that is exposed to the ambient environment is emphasized, the influence of wall thickness and material of the drillpipe on the stress state of drillstring is also discussed. The numerical results show that significant fluctuations in cross-sectional stress occur during the riserless drilling process, particularly under varying hydrodynamic loads; the tensile stress and effective stress are larger on landing string and the maximum values of these stresses occur at the connection point of the landing string and casing string; the bending stress is larger on casing string and the maximum value occurs near the sea floor; and increasing the wall thickness and selecting the low-density material can help to reduce the stress of the drillstring. It can be concluded from the numerical results that during the CwD riserless drilling process, the effective stress on the cross section of drillstring is mainly determined by the tensile stress and the contribution of bending stress is comparably small, and the dangerous cross section of the drillstring is located at the connection point of landing string and casing string. The proposed dynamic model offers theoretical insights that can inform drillstring design and vibration mitigation strategies in CwD operations.